Supporting Knowledge Management and Organisational Learning in Multinational Coorporations - Travis, Julie; Venable, John (Turku Centre for Computer Sciece, 1998)
Management of Organisational Learning and Knowledge is a complex and difficult task. Doing so within the context of a multinational corporation presents even more difficulties. Like many large organisations, most multinational organisations are highly distributed. This presents problems in terms of the inability to get groups of people together for group activities concerning knowledge management and organisational learning. The highly distributed organisation also presents difficulties in disseminating knowledge from one part of an organisation to other parts. Multinational organisations also commonly contain a variety of different cultures. The cultural differences can occur at a number of different levels, between individuals, between the individual and the organisational unit, between different organisational units, and between countries. In this paper, we propose a number of ways of addressing these difficulties for facilitating knowledge management and organisational learning in the multinational organisation, including the use of adaptable systems thinking approaches, group support systems, and digital library technologies. In particular, we propose using these technologies in combination as a way of addressing the twin difficulties of the highly distributed and culturally differentiated organisations that multinational organisations often are.